The Impact of Expectations, Match Importance, and Results in the Stock Prices of European Football Teams - Godinho, P. (2016)
We analyse the relation between stock returns and results in national league matches for 13 clubs of six European countries. We assume that the stock prices should only respond to the unexpected component of match results, and we use betting odds to separate the expected component of results from the unexpected one. We consider both the unweighted results and the results weighted by a new measure of match importance that we propose. When this measure is used, a significant relation between the results and stock performance is found for most teams.